2007
DOI: 10.1016/j.tsf.2006.12.138
|View full text |Cite
|
Sign up to set email alerts
|

CdTe photovoltaics: Life cycle environmental profile and comparisons

Abstract: We discuss the emissions of cadmium throughout all the life stages of CdTe PV modules, from extracting, refining, and purifying the raw materials to producing, using, and disposing or recycling of the modules. Then, we compare these emissions with those in the life cycle of three different types of crystalline Si PV modules. The energy requirement and energy pay back times (EPBT) of CdTe PV modules are considerably shorter than that of crystalline Si modules, although the latter exhibit higher efficiencies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 6 publications
1
28
0
Order By: Relevance
“…Figure 3 shows the flowchart of the life cycle for a solar photovoltaic system. The stages of the life cycle of the generation of this type of energy are: (i) the extraction of raw materials, (ii) processing and purification, (iii) module manufacturing (balance of system) and its components, (iv) the installation and use of systems and (v) Dismantling and disposal or recycling [18]. In each phase are taken as inputs materials (M) and a quantity of heat or specific energy (Q), spent on the operation or thread, and delivering as a final result a surplus of emissions (E), that they are thrown into the environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 shows the flowchart of the life cycle for a solar photovoltaic system. The stages of the life cycle of the generation of this type of energy are: (i) the extraction of raw materials, (ii) processing and purification, (iii) module manufacturing (balance of system) and its components, (iv) the installation and use of systems and (v) Dismantling and disposal or recycling [18]. In each phase are taken as inputs materials (M) and a quantity of heat or specific energy (Q), spent on the operation or thread, and delivering as a final result a surplus of emissions (E), that they are thrown into the environment.…”
Section: Resultsmentioning
confidence: 99%
“…After cementation with copper, the CdTe is leached with caustic soda to produce a solution of sodium tellurium used to obtain Te y TeO2. This gives to Cd and Te semiconductive characteristics [18] [19]. In some research the application of life-cycle assessment builds on the CED indicator (Cumulative Energy Demand) as it is proposed by Battisti y Corrado (2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of environmental impacts other than greenhouse gas emissions, Fthenakis and Kim [257] find that CdTe PV technologies emit less cadmium throughout their life cycle than coal-and oil-fired power plants. In a dynamic LCA, Pehnt [30] projects future life-cycle impacts of PV to decrease by about 40% until 2030.…”
Section: Life-cycle Characteristicsmentioning
confidence: 99%
“…Modules reported that though toxicity is a major concern for some thin film PV technologies, the cadmium emissions to air on a per kWh basis are higher from coal and the European energy mix [19], [20].…”
mentioning
confidence: 99%